Coronavirus Disease 2019 and Bone Marrow Transplantation: A Mini-review - Beuy Joob; Viroj Wiwanitkit (Wolters Kluwer Medknow Publications, 2024)
Since the first incidence of coronavirus disease 2019 (COVID-19) was identified in 2019, the illness has rapidly spread, increasing the number of cases, hospital admissions, and fatalities associated with COVID-19. The epidemic is putting an unprecedented amount of stress on the health-care system, including programs that perform both allogeneic and autologous hematopoietic stem cell transplantation (HSCT) and cellular treatment employing T cells. The risk of a severe COVID-19 infection in HSCT patients is widely acknowledged, and the COVID-19 vaccine is strongly advised. This mini-review provides a succinct overview of recent advances in COVID-19 and bone marrow transplantation.